Unpaid Application-Based Learning Video Production with Teachers - Harjito, Harjito; Kadarwati, Sri; Nuswowati, Murbangun; Kasmui, Kasmui; Asmorowati, Dian Sri; Mubarak, Dinda Halimah Agrifani; Damayanti, Yosephine Debbie; Rohmah, Rojaa Maysa (Universitas Negeri Semarang, 2023)
Students at SMA Negeri 1 Subah, Batang Regency, Central Java, in the post-pandemic era , need auxiliary media that can be widely accessed , are timeless , and are needed to support face-to-face learning in class, such as learning videos . Auxiliary media This can developed and produced alone by the teacher without must relying on digital platforms such as YouTube. However, only a small number of teachers at SMA Negeri I Subah have been able to develop and produce learning videos. Because yes , activities This aim For accompany all the teachers subjects at SMA Negeri 1 Subah for develop and produce learning videos through systematic and comprehensive steps. This activity includes several important stages, namely: (1) recognizing and compiling learning video scripts, (2) practicing the basics of Open Broadcaster Software (OBS), (3) producing videos based on scripts, (4) modifying learning videos into interactive videos using H5P, and (5) dissemination of results. This activity ends with an assessment and evaluation of the learning videos produced at the end of the activity and the overall implementation of the activity. The results of this activity show that the number of teachers is capable develop and produce learning videos experience improvement , though Not yet significant . Learning videos produced by teachers have been fulfil terms , though Still need improved the quality . Motivation and support from schools and parties related need improved so that teachers continue enthusiastic produce quality learning video products.